Phylogeography and morphological variation of the branching octocoral Pseudopterogorgia elisabethae - Gutiérrez-Rodríguez, Carla; Barbeitos, Marcos S.; Sánchez, Juan A.; Lasker, Howard R. (Molecular phylogenetics and evolution, 2009)
Coral reef anthozoans exhibit extensive morphological variation across and within environmental clines making it difficult to define species boundaries. The relative contributions of genetic variation and ecophenotypic plasticity to the observed phenotypic variation are unknown in most cases. The branching octocoral Pseudopterogorgia elisabethae is widely distributed throughout the Caribbean and colonies vary in appearance within and among populations. We performed genetic and morphological analyses of P. elisabethae from multiple locations within the Bahamas, as well as a Florida Keys and a distant western Caribbean location to determine the levels of genetic and morphological variation (colony form and sclerites characteristics) across populations from different sites, and assessed whether there was congruence between the genetic and morphological variation. Based on sequences of the internal transcribed spacer region of the ribosomal DNA, four groups were found that generally correspond to the geography of the Bahamas. Morphometric analysis of branch and branchlet characteristics indicated that colonies from two of the sites differed from the rest, but there was no clear correspondence between genetic and morphological variation. In general, there were no qualitative differences in the sclerites from the different populations. However, there were some differences in the dimensions of scaphoids and rods of colonies from different sites. This study has shown that P. elisabethae displays genetic and morphologic variation among some populations of the Bahamas, Florida and San Andres, Colombia. P. elisabethae is harvested in the Bahamas and these findings should be considered in management plans and conservation efforts for the species.